(untitled) (Intersections of Faith and Culture: American Journal of Religious and Cultural Studies (2993-2599), 2025)
Teaching German as a second foreign language (L3, typically after English as L2) requires approaches that account for learners’ existing multilingual competence, potential transfer effects, and distinct motivational profiles. This enhanced article provides a comprehensive review of innovative pedagogical methods, including multilingual contrastive didactics (e.g., Deutsch als Fremdsprache nach Englisch – DaFnE), task-based language teaching (TBLT), content and language integrated learning (CLIL), flipped classroom models, collaborative and project-based learning, and advanced digital integrations such as augmented reality (AR), virtual reality (VR), artificial intelligence (AI)-driven tools, and gamification. Empirical evidence from recent studies demonstrates improved proficiency, metacognitive awareness, motivation, and intercultural competence. An expanded table details methods, implementation strategies, benefits, challenges, and supporting research. Recommendations emphasize teacher training and hybrid models to optimize outcomes in diverse educational contexts.